The Relationship Among Between Serum Cytokine, Intact PTH, Osteocalcin and Bone Mineral Density Values in Postmenopausal Women - M. Yıldız; S. Kokino; N. Turan (Galenos Yayinevi, 2002)
This study was designed to compare the bone mineral density (BMD) in 108 postmenopausal women with laboratory data including osteocalcin, intact parathyroid hormone and serum cytokine values. One hundred eigth postmenopausal women were randomly divided into 3 sub groups according to their BMD and medical treatment. The first group consisting of 18 postmenopausal women had no osteoporosis, mean age and mean duration of postmenopausal period were 52.94± 4.90 and 6.5±4.76 years respectively. The second group consisting of 15 postmenopausal women had osteoporosis and was not treated, mean age and mean duration of postmenopausal period were 53.60±8.84 and 9.73± 6.75 years respectively. The third group consisting of 75 postmenopausal osteoporotic women was under medical treatment, mean age nd mean duration of postmenopausal period were 58.52±8.51 and 13.20±8.41 years respectively. Bone mineral density at femur Ward's triangle, trochanter and lumbar spine t score values were evaluated by dual X ray absorptiometry (DXA). Serum calcium, phosphorous, C-reactive protein, erythrocyte sedimentation rate, cytokines (interleukin-1, IL-1, interleukin-2, IL-2, interleukin-6, IL-6, interleukin-8, IL-8 and tumor necrosis factor alpha TNF-a), osteocalcin, intact parathyroid hormone were measured. In subjects, no significant correlation was observed between BMD t scores of lumbar spine, trochanter, Ward's triangle and cytokine values. On the other hand, among these groups significant difference was found between age, treatment duration, t scores of lumbar spine, trochanter, Ward's triangle and postmenopausal period, but not between IL-1, IL-2, IL-6, IL-8, TNF-a, osteocalcin, intact parathyroid. As a conclusion we think BMD (especially in the early postmenopausal period) might be correlating with the levels of cytokines in bone microenvironment rather than serum levels. In the early postmenopausal osteoporosis period serum IL-6 value might be supporting to follow medical treatment efficiency.